Using Networked Ontologies to support UX Evaluation in Immersive Context - Costa, Simone Dornelas; Manso, Carolina De Freitas; Marques, Leonardo Carneiro; Gadelha, Bruno Freitas; Conte, Tayana Uchôa; Barcellos, Monalessa Perini (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Over the past few years, new interactive systems such as immersive technologies have gradually permeated our daily lives and found adoption across various fields. Immersive technologies provide users with immersive experiences. Assessing and modeling the quality of such experiences has become a trending topic in HCI, and UX is a key quality attribute in this context. When it comes to immersive experiences, evaluating UX is particularly challenging because the user should not be interrupted to provide feedback. In this paper, we propose using networked ontologies to support evaluating immersive experiences. We have explored using ontologies from an ontology network addressing the HCI domain to develop a tool that supports UX experts evaluating such experiences based on data recorded in interaction logs. We used the ontology-based tool to evaluate the UX of an immersive application that supports collaborative music composition. The tool extracted data from the application interaction logs applied UX metrics, and provided consolidated data and information in graphs and tables. We conducted a study and collected feedback from the tool developer and three UX experts who used the tool. Results showed that using networked ontologies to develop a tool to support UX evaluation is feasible and valuable. In summary, the ontologies helped at the conceptual level by offering a basis to define the system's structural model and at the implementation level by assigning semantics to data to make inferences about UX. Based on the UX experts' perceptions, the tool was considered a promising system, beneficial, helpful, and easy to use.